Identification of a distinct lineage of aviadenovirus from crane feces - Mukai, Yahiro; Tomita, Yuriko; Kryukov, Kirill; Nakagawa, So; Ozawa, Makoto; Matsui, Tsutomu; Tomonaga, Keizo; Imanishi, Tadashi; Kawaoka, Yoshihiro; Watanabe, Tokiko; Horie, Masayuki (Virus genes, 2019)
Viruses are believed to be ubiquitous; however, the diversity of viruses is largely unknown because of the bias of previous research toward pathogenic viruses. Deep sequencing is a promising and unbiased approach to detect viruses from animal-derived materials. Although cranes are known to be infected by several viruses such as influenza A viruses, previous studies targeted limited species of viruses, and thus viruses that infect cranes have not been extensively studied. In this study, we collected crane fecal samples in the Izumi plain in Japan, which is an overwintering site for cranes, and performed metagenomic shotgun sequencing analyses. We detected aviadenovirus-like sequences in the fecal samples and tentatively named the discovered virus crane-associated adenovirus 1 (CrAdV-1). We determined that our sequence accounted for approximately three-fourths of the estimated CrAdV-1 genome size (33,245 bp). The GC content of CrAdV-1 genome is 34.1%, which is considerably lower than that of other aviadenoviruses. Phylogenetic analyses revealed that CrAdV-1 clusters with members of the genus Aviadenovirus , but is distantly related to the previously identified aviadenoviruses. The protein sequence divergence between the DNA polymerase of CrAdV-1 and those of other aviadenoviruses is 45.2–46.8%. Based on these results and the species demarcation for the family Adenoviridae , we propose that CrAdV-1 be classified as a new species in the genus Aviadenovirus . Results of this study contribute to a deeper understanding of the diversity and evolution of viruses and provide additional information on viruses that infect cranes, which might lead to protection of the endangered species of cranes.